EDUchallenge - Orel, Mojca (knjige, 2023)
The Book of Papers bring together 53 scientific and professional papers and 25 lecture abstracts, empowered by the dedication of experienced teachers and researchers from around the world. By reading these articles, you will discover how they have faced challenges and honed their teaching skills, and explore their crucial impact on success in today's ever-changing world.The articles you will read offer practical examples and effective solutions for teaching and for evaluating knowledge. They describe the use of artificial intelligence and reflect the importance of integrating soft skills into educational processes, recognising that these are key skills that students and learners need for a successful future.
Keywords: izobraževalna tehnologija; Izobraževanje; jezikovni pouk; književnost; komuniciranje; osebnostni razvoj; Posvetovanja; pouk; trajnostni razvoj; učenje; zborniki